A MoS2 based silver-doped ZnO nanocomposite and its antibacterial activity against β-lactamase expressing Escherichia coli. Issue 12 (2nd March 2022) - Naskar, Atanu; Shin, Joonho; Kim, Kwang-sun
Abstract : Synthesis and activity of a MoS2 based nanoplatform. Abstract : Multidrug-resistant (MDR) Gram-negative bacteria including Escherichia coli are increasingly resistant to current antibiotics. Among the strategies implemented to eradicate such MDR pathogens, approaches based on two-dimensional (2D) nanomaterials have received considerable attention. In particular, the excellent physicochemical properties of 2D molybdenum disulfide (MoS2 ) nanosheets, including a high surface area, good conductivity, and good surface retention, are advantageous for their use as bactericidal agents. Herein, we report the fabrication of a MoS2 -based nanocomposite conjugated with silver-doped zinc oxide (AZM) as an effective antibacterial agent against E. coli species. The properties of AZM were characterized, and its antibacterial activity against MDR E. coli strains with different resistance types was evaluated. MoS2 was found to activate the antibacterial activity of AZM and provide enhanced selectivity against MDR E. coli strains expressing β-lactamases. We proposed that membrane disruption of bacterial cell walls was the major cell death mechanism for MDR E. coli . Furthermore, surface charge perturbation could explain the differences in AZM activity against MDR E. coli strains expressing a β-lactamase and a mobilized colistin resistance ( mcr-1 ) gene product. Thus, a MoS2 -based nanocomposite with a functional conjugation strategy could be a selective nano-antibacterial platform against infections caused by MDR E. coli with resistance against β-lactam antibiotics.